2008
DOI: 10.1037/0012-1649.44.4.983
|View full text |Cite
|
Sign up to set email alerts
|

Infant discrimination of faces in naturalistic events: Actions are more salient than faces.

Abstract: Despite the fact that faces are typically seen in the context of dynamic events, there is little research on infants' perception of moving faces. L. E. Bahrick, L. J. Gogate, and I. Ruiz (2002) demonstrated that 5-month-old infants discriminate and remember repetitive actions but not the faces of the women performing the actions. The present research tested an attentional salience explanation for these findings: that dynamic faces are discriminable to infants, but more salient actions compete for attention. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 115 publications
(206 reference statements)
5
55
0
Order By: Relevance
“…This pattern is consistent with other studies showing that infants at this age are more attentive to the dynamic properties of events, such as action, than to relatively static properties, such as object appearance (Bahrick, Gogate, & Ruiz, 2002;Bahrick & Newell, 2008;Perone et al, 2008). We did not find here that infants' dishabituation to a novel appearance was significantly less than their dishabituation to a change in action, t(17) ¼ 1.37, p ¼ .19, d ¼ 0.32, or to a change in sound, t(17) ¼ 1.07, p ¼ .30, d ¼ 0.25.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern is consistent with other studies showing that infants at this age are more attentive to the dynamic properties of events, such as action, than to relatively static properties, such as object appearance (Bahrick, Gogate, & Ruiz, 2002;Bahrick & Newell, 2008;Perone et al, 2008). We did not find here that infants' dishabituation to a novel appearance was significantly less than their dishabituation to a change in action, t(17) ¼ 1.37, p ¼ .19, d ¼ 0.32, or to a change in sound, t(17) ¼ 1.07, p ¼ .30, d ¼ 0.25.…”
Section: Resultssupporting
confidence: 92%
“…For example, there may be a general bias for infants to attend to dynamic features such as actions over static features such as the appearance of objects. Indeed, Bahrick and colleagues observed that 5.5-and 7-month-old infants selectively attend to the actions of an actress, apparently ignoring the features of her face (Bahrick et al, 2002;Bahrick & Newell, 2008). Based on such findings, Bahrick and colleagues propose an attentional salience hypothesis in which actions are more easily and quickly discriminated than static features in events that feature both kinds of information.…”
Section: Discussionmentioning
confidence: 93%
“…Why might this be the case? Research suggests that actions (and changes in actions) may simply be more salient than faces and/or agent changes (Bahrick, Gogate & Ruiz, 2002; Bahrick & Newell, 2008). Alternatively, a quickly subsiding novelty response, like the one seen in our actor discrimination trial, may actually be an indicator of increased sensitivity to actor identity as opposed to decreased sensitivity (Quinn & Intraub, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They also found that 5-month-olds could recognize faces when familiarized with static faces. The results suggested that motion signals might distract infant attention from processing facial information properly, thereby leading to a non-preference (Bahrick, Lickliter, & Castellanos, 2013; Bahrick & Newell, 2008). Additional studies have indicated that presenting dynamic talking faces results in neonates preferring a familiar face over a novel face, whereas a static face familiarization procedure led to a novelty preference (Coulon, Guellaï, & Streri, 2011; Guellaï, Coulon, & Streri, 2011).…”
mentioning
confidence: 99%